A study on the use of visual aids in teaching English to the first-year students at Military Technical Academy = Nghiên cứu cách sử dụng giáo cụ trực quan trong việc dạy tiếng Anh cho sinh viên năm thứ nhất Học viện kỹ thuật quân sự. M.A Thesis Linguistic - Lê, Hoàng Mai (University of Languages and International Studies, 2017)
39 p. + CD-ROM + tóm tắt